Bara olyckliga omständigheter - en kvalitativ studie om hemlösa kvinnor. - Göransson,Malin; Telemo,Julia (2012)
This is a kvalitative study, focused on homeless women, and their ability to cope with their current situation, and what strategies they are using. The study is based on seven interviews with homeless men and women in Helsingborg, Sweden. The focus is whether this group of women feel that they are in control of their own lifesituation, and whether or not they have certain strategies to manage their everyday lives. The interviews are analysed with the help of theory of norms, intersectionality and feminist theory. We found that the homeless women in Helsingborg have different life stories, but that physical abuse and domestic violence was a regular feature. Both men and women in the interviews also stated that they were reluctant to report crimes. And the women showed a variety of strategies in their everyday life.
Keywords: Homeless women; intersectionality; feminist theory; norms.